A Decision Modelling Approach for Perceived and Engaged Immersive Visual Interactive Applications on the Metaverse - IBRAHIM, SAMAR (2024)
Many researchers have developed and implemented various immersive visual interactive applications that incorporate visualization and interaction techniques, support the visual construct and enhance exploration in the Metaverse. Benchmarking these applications is critical due to the absence of an ideal model, particularly given their varied development criteria. The multiple evaluations, significance, and the data variability of these criteria among various applications present challenges that necessitate using specific multicriteria decision-making (MCDM) methods. This study introduces a new decision modelling approach that extends the fuzzy-weighted zero inconsistency (FWZIC) method with the new Interval-Valued Fermatean Neutrosophic fuzzy sets (IVFN) and combines it with the extended ranking method, Više kriterijumska Optimization I compromise Rešenje (VIKOR) and Gray relational analysis (GRA). The modelling approach benchmarks the most perceived immersive visual interactive applications using the extended VIKOR-GRA method based on a decision matrix of 18 criteria and 29 alternatives for the four visualization scenarios. The new extended IVFN-FWZIC method weighs the criteria for benchmarking the optimal applications based on experts’ judgments. The results illustrate the effectiveness of the modelling approach and indicate that "spatial" and “haptics” are the most significant criteria in evaluating immersive visual interactive applications. The robustness and reliability of the results were validated and evaluated using sensitivity analysis, comparative analysis, and a systematic ranking process. This study offers a vision for decision-makers and stakeholders, contributing to improving visualization and exploration of the Metaverse.